The Iconography of the Relief Sculpture of the Buddha’s Biography: The Temptation Episode by Mara from the Lintel of Phimai Sanctuary: ประติมานวิทยาของภาพสลักพุทธประวัติตอนมารผจญ จากทับหลังปราสาทพิมาย - Hongcharoen, Thawisak; Chakamanont, Sirin; Chinapatthanawong, Nutthariya (Mekong-Salween Civilization Studies Journal, 2025)
This research aims to study and analyze religious symbolism, focusing specifically on the relief sculpture of the Buddha’s biography in the Temptation of Mara episode found on the lintel of Phimai Sanctuary. The study adopts a non-empirical qualitative research methodology, gathering data from related documents and literature while utilizing iconographic theory as the principal framework for interpretation. The findings reveal that iconography serves as a vital tool in understanding the symbolic dimensions of religious art, particularly in the depiction of the Buddha overcoming Mara and his retinue. This portrayal emphasizes core Mahayana Buddhist principles, illustrating the Buddha’s victory through calmness and wisdom. Symbolically, it represents the transcendence of internal obstacles and the attainment of enlightenment, highlighting the spiritual battle against defilements. Additionally, the study shows that the Victory Over Mara lintel reflects the diffusion of Buddhism during the Khmer Empire and stands as a significant marker of the interrelationship between art and religion in that historical context.